2005
DOI: 10.1007/s00268-004-7533-y
|View full text |Cite
|
Sign up to set email alerts
|

High Body Mass Index as a Possible Risk Factor for Pilonidal Sinus Disease in Adolescents

Abstract: Pilonidal sinus disease (PSD) is common in adults, but it may also develop in adolescents. The intergluteal groove is a deep moist area in which broken hairs and foreign bodies can collect, often leading to infection. Only a few papers have been published considering PSD in children. For the present study, we retrospectively examined the data of operated patients with PSD. From that review, it appears that high body mass index (BMI) might be a risk factor for the development of PSD and its complications in old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 16 publications
1
34
2
3
Order By: Relevance
“…In our results, there is significant shorter healing time in closed methods than open methods. Also we discussed the technique of the surgical procedure to each patient and explained the (2005) suggested that high BMI is a significant risk factor in the development of both symptoms and complications of PSD after surgical treatment [17]. We agree with Arda's suggestion that surgical treatment of PSD in obese patients was associated with delayed healing in some surgical procedures compared with nonobese patients.…”
Section: Discussionsupporting
confidence: 63%
“…In our results, there is significant shorter healing time in closed methods than open methods. Also we discussed the technique of the surgical procedure to each patient and explained the (2005) suggested that high BMI is a significant risk factor in the development of both symptoms and complications of PSD after surgical treatment [17]. We agree with Arda's suggestion that surgical treatment of PSD in obese patients was associated with delayed healing in some surgical procedures compared with nonobese patients.…”
Section: Discussionsupporting
confidence: 63%
“…8,[20][21][22] Cubukcu et al 23 did not detect a statistical significance between BMI and PSD. Because of the deeper structure of the intergluteal cleft and the fragility with wetness as a result of oversweat, obese people are more vulnerable to PSD.…”
Section: Discussionmentioning
confidence: 99%
“…Pilonidal sinus (PS) is a common surgical disease, referring to a midline hair-containing sinus in the natal cleft (1). It is associated with a high recurrence rate, risk of infection and abscess formation (2).…”
Section: Introductionmentioning
confidence: 99%